Public-Private Partnerships in Infrastructure Development: Governance, Financing, and Sustainability Challenges - Handayani, Indah Try; Taufiqurokhman (Politeia : Journal of Public Administration and Political Science and International Relations, 2025)
Public-Private Partnerships (PPPs) have gained prominence as mechanisms to address global infrastructure deficits and support sustainable development. This narrative review examines governance, financing, environmental, and social dimensions of PPP implementation across diverse contexts. Literature was systematically collected from Scopus, Web of Science, and Google Scholar using targeted keywords and Boolean search strings, applying inclusion and exclusion criteria to ensure relevance. Empirical and theoretical studies were synthesized to identify thematic insights. Findings demonstrate that governance frameworks, including clear roles, accountability, and transparency, are critical to PPP success, while political instability, weak institutions, and corruption hinder effectiveness. Financing models such as Build-Operate-Transfer and joint ventures effectively mobilize capital but require balanced risk distribution to prevent inefficiencies. Environmental sustainability is increasingly embedded in PPP projects, particularly through renewable energy and climate-resilient infrastructure, though integration remains uneven across regions. Social outcomes are mixed: developed countries often achieve inclusivity and accessibility, whereas developing countries face equity challenges when profitability dominates. The discussion emphasizes that systemic factors, innovative financing models, and stakeholder engagement significantly shape outcomes. This review concludes that advancing PPP frameworks requires embedding sustainability and equity into governance and contractual arrangements, supported by anti-corruption measures and adaptive financing strategies. Future research should prioritize integrated evaluative frameworks and comparative analyses across regions. By aligning governance quality, financial innovation, and social inclusiveness, PPPs can play a transformative role in achieving sustainable infrastructure and national development goals.